Competition Dynamics of Market Share for Assets in the Banking Industry Using the Lotka-Volterra Model Approach - Sri Wahyuni Jamal; Suparno Suparno; Umi Kartini Rashid; Fenty Fauziah (Faculty of Economic and Business, 2024)
Research Originality: Competition in the banking sector is unavoidable. Such competition is present among state-owned banks in Indonesia. In contrast to the previous studies that did not include the competition type and its stability, this study includes the competition type and its stability in the estimation.Research Objectives: This study aims to discover the competition type and its stability, and to forecast the market share among the four state-owned banks.Research Methods: Using market share data of assets published annually by each of the banks from 2010 to 2023, the study employs the Lotka-Volterra model approach to analyze the competition type and its stability that occur among the four state-owned banks.Empirical Results: The study discovers that the competition types of the four state-owned banks vary. There have been three competition types among the four state-owned banks: mutualism, predator-prey and pure competition. Besides, the stability property of the four state-owned banks tended to be unstable. By looking at the gains of market share for assets, only Mandiri’s market share gains will increase in the 2024-2028 period. As a result, the total market share gains for the four state-owned banks declined sequentially.Implications:This research holds significance for four state-owned banks in Indonesia as it provides valuable insights into considering the three competition types (mutualism, pure competition and predator-prey) as the primary key to achieving a significant market share value.JEL Classification: C61, D41, E17, G21How to Cite:Jamal, S. W., Suparno., Rashid, U. K., & Fauziah, F. (2024). Competition Dynamics of Market Share for Assets in the Banking Industry Using the Lotka-Volterra Model Approach. Etikonomi, 23(2), 299 – 316. https://doi.org/10.15408/etk.v23i2.32226